2010
DOI: 10.1007/s11999-009-0963-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Pain Catastrophizing Predicts Pain Outcome after Knee Arthroplasty

Abstract: Psychologic status is associated with poor outcome after knee arthroplasty yet little is known about which specific psychologic disorders or pain-related beliefs contribute to poor outcome. To enhance the therapeutic effect of a psychologic intervention, the specific disorders or pain-related beliefs that contributed to poor outcome should be identified. We therefore determined whether specific psychologic disorders (ie, depression, generalized anxiety disorder, panic disorder) or health-related beliefs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
296
5
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 343 publications
(330 citation statements)
references
References 50 publications
(121 reference statements)
17
296
5
4
Order By: Relevance
“…Lingard and Riddle [34] estimated the effect to be 3 to 5 points lower on the 20-point pain component of the WOMAC, indicating worse pain in the group of patients with lower mental health scores. Two studies [39,47] that examined the correlation between patient pain after TKA and the Pain Catastrophizing Scale found a statistically significant relationship. Riddle et al [39] found that a Pain Catastrophizing Scale score of 16 or greater predicted less than 50% improvement in WOMAC pain score (odds ratio [OR], 2.67; 95% CI, 1.2 À 6.1; p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lingard and Riddle [34] estimated the effect to be 3 to 5 points lower on the 20-point pain component of the WOMAC, indicating worse pain in the group of patients with lower mental health scores. Two studies [39,47] that examined the correlation between patient pain after TKA and the Pain Catastrophizing Scale found a statistically significant relationship. Riddle et al [39] found that a Pain Catastrophizing Scale score of 16 or greater predicted less than 50% improvement in WOMAC pain score (odds ratio [OR], 2.67; 95% CI, 1.2 À 6.1; p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
“…There was 89% agreement in the quality rating between the two investigators. Only two studies justified their sample size and provided a power analysis [39,44]. All studies had a minimum 6-month followup period.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations